Decolonising legal education in South Africa: Is it time to press the reset button? (Journal of Decolonising Disciplines, 2021)
South Africa has, like many other African countries, inherited a foreign legal system. The democratic Constitution of 1996 altered the country’s legal framework such that it became reflective of societal change, while recognising plurality in South African legal culture(s). Owing to the 2015‒2016 #FeesMustFall student protests, another ideological shift in legal education is being precipitated by the changing socio‒political landscape of the country. This shift is framed as decolonisation, which entails shedding the colonial yoke of exclusive western ideologies and thinking, thereby requiring an inclusive educational approach. Such a transformed education would incorporate local African traditions, customs and ideologies that existed prior to colonial imposition. Legal thinking and culture is dependent on legal education, and legal education is consequently reliant on the legal framework. Considering this chain of influences, I argue that decolonisation cannot be achieved merely as a change in legal education alone: it requires an ideological shift in the country’s legal framework.
Keywords: Legal education; decolonisation; legal history; indigenous law; customary law